High antibody titres against predicted Mycoplasma surface proteins do not prevent sequestration in infected lung tissue in the course of experimental contagious bovine pleuropneumonia - Schieck, Elise; Liljander, Anne M.; Hamsten, Carl; Gicheru, Nimmo; Scacchia, Massimo; Sacchini, Flavio; Heller, Martin; Schnee, Christiane; Sterner-Kock, Anja; Hlinak, Andreas; Naessens, Jan; Poole, Elizabeth J.; et al. (Elsevier, 2014)
Contagious bovine pleuropneumonia (CBPP), a severe respiratory disease of cattle caused by Mycoplasma mycoides subsp. mycoides (Mmm) is endemic in many African countries due to fragmented veterinary services and the lack of an efficient vaccine and sensitive diagnostics. More efficient tools to control the disease are needed, but to develop the tools, a better understanding of host-pathogen interactions is necessary. The aim of this study was to characterize the kinetics of the humoral immune response against 65 Mmm surface antigens for an extended period in cattle that survived a primary infection with Mmm. We describe clinical and haematological outcomes, and dissect the humoral immune response over time, to specific antigens and compared the antibody responses between different pathomorphological outcomes. No antigen-specific antibodies correlating with protection were identified. Interestingly we found that animals that developed Mycoplasma-containing sequestra had significantly higher antibody levels against proteins comprising the surface proteome than the animals that cleared Mycoplasma from their lungs. Based on these data we suggest that high antibody titres might play a role in the establishment of pathomorphological changes, such as vasculitis, which should be investigated in future studies. Beneficial antibody specificities and cellular immune responses need to be identified in order to foster the development of an improved vaccine in the future.